1994
DOI: 10.1557/jmr.1994.1742
|View full text |Cite
|
Sign up to set email alerts
|

Effects of boron on the deformation behavior of Ni3Al

Abstract: The effects of boron additions (0 to 4000 wppm B) on the room temperature deformation behavior of Ni-24Al have been examined with both quasi-static deformation and short pulse duration shock loading. Changes in compressive yield strength and hardness with the amount of boron suggest that strengthening effects are more complicated than predicted by usual interstitial solid-solution strengthening considerations. The nature of the dislocations changes from SISF-dissociated superdislocations in the Ni-24Al base al… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2002
2002
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 17 publications
(4 citation statements)
references
References 40 publications
0
4
0
Order By: Relevance
“…Besides the powder metallurgy process, ,, adding intrinsic high-mechanical-strength nanoparticles like nano-SiC in the Bi 2 Te 3 -based alloys has also been reported to enhance their mechanical performance. , Generally, metal borides possess remarkable intrinsic mechanical properties especially the super hardness, and adding a small amount of boron in various alloys can also greatly improve their mechanical strength. MgB 2 is one of the most popular metal borides because of its superconducting properties, which may be peculiar for tuning the thermoelectric properties of Bi 2 Te 3 -based alloys. In this work, a slight amount of MgB 2 is doped in the n-type Bi 2 Te 2.7 Se 0.3 alloys to suppress the donor-like effect from the spark-plasma-sintering process and to concurrently increase the hardness.…”
Section: Introductionmentioning
confidence: 99%
“…Besides the powder metallurgy process, ,, adding intrinsic high-mechanical-strength nanoparticles like nano-SiC in the Bi 2 Te 3 -based alloys has also been reported to enhance their mechanical performance. , Generally, metal borides possess remarkable intrinsic mechanical properties especially the super hardness, and adding a small amount of boron in various alloys can also greatly improve their mechanical strength. MgB 2 is one of the most popular metal borides because of its superconducting properties, which may be peculiar for tuning the thermoelectric properties of Bi 2 Te 3 -based alloys. In this work, a slight amount of MgB 2 is doped in the n-type Bi 2 Te 2.7 Se 0.3 alloys to suppress the donor-like effect from the spark-plasma-sintering process and to concurrently increase the hardness.…”
Section: Introductionmentioning
confidence: 99%
“…This result suggests that boron is an effective element to eliminate the annealing twins. Brusso and Mikkola 27) had also obtained a similar result that boron addition greatly reduces the number of annealing twins in recrystallized Ni-24Al alloy.…”
Section: Effect Of Boron Addition On Annealing Twinsmentioning
confidence: 70%
“…The remarkable effect of boron addition on eliminating annealing twins observed in experiment supports the asymmetrical twinning in boron-doped Ni 3 Al where boron atoms act as a potent obstacle to twinning and generation of SISFs or movement of 1/3 211 superpartial dislocations. Baker et al 40) showed a trace of boron addition makes SISFs disappear in Ni 3 Ga. Brusso and Mikkola 27) reported that addition of boron decreases the frequency of annealing twinning events in Ni-24Al after heavy deformation and recrystallization.…”
Section: Annealing Twinning Process In Boron-doped L1mentioning
confidence: 99%
See 1 more Smart Citation